2019
DOI: 10.17921/2447-8938.2019v21n4p409-13
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Strength Training on Scapular Dyskinesia: A Systematic Review

Abstract: Scapular dyskinesia refers to the functional disorder that affects  the shoulder complex. Strength training has recently been used as a non-pharmacological strategy to minimize functional disorders that affect the musculoskeletal system. However, the evidence pointing to the contributions of strength training on scapular dyskinesia is still poorly understood. Therefore, the objective of the present study was to systematically review the evidence on the effects of strength training on scapular dyskinesia. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
5
0
2
Order By: Relevance
“…Blackburn’s scapula stabilization exercise is commonly used by physiotherapists, and it has been reported that there is a significant difference [ 31 ] before and after the exercise in terms of muscle strength improvement of the rotator cuff in shoulder joints. However, as scapula dyskinesis is a disorder involving changes in the entire shoulder complex and all shoulder lesions, muscle strengthening of the rotator cuff is not adequately efficient [ 17 ]. Therefore, movement control exercises should be conducted considering kinematic aspects rather than unconditional muscle strengthening exercises.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Blackburn’s scapula stabilization exercise is commonly used by physiotherapists, and it has been reported that there is a significant difference [ 31 ] before and after the exercise in terms of muscle strength improvement of the rotator cuff in shoulder joints. However, as scapula dyskinesis is a disorder involving changes in the entire shoulder complex and all shoulder lesions, muscle strengthening of the rotator cuff is not adequately efficient [ 17 ]. Therefore, movement control exercises should be conducted considering kinematic aspects rather than unconditional muscle strengthening exercises.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, a systematic literature review on scapula dysfunction reported the following as the main causes of scapula dysfunction: reduced rotator cuff muscle strength, weak scapula muscles, reduced range of motion (ROM) of the shoulder and shoulder joints, lesions in soft tissue, inadequate movement of the scapula, and increased risk of shoulder joint impact [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if the stabilizing muscles of the scapula are weakened or the shoulder performance is impaired, the normal position and kinematics of the scapula would change [ 23 ]. Samir et al, [ 50 ] stated that muscle strengthening is a potential intervention strategy to improve recovery and prevent shoulder dysfunction. On the other hand, some exercises applied in the current study have caused proximal stability in shoulder joint and created a stable support for proper performance of the upper extremity.…”
Section: Discussionmentioning
confidence: 99%
“…Essas alterações na escápula, mesmo sem uma causa específica identificada, estão frequentemente associadas a várias comorbidades relacionadas ao ombro, como tendinites do manguito rotador ou acidentes de trabalho. Qualquer movimento anormal na escápula é definido como discinesia escapular, o que, muitas vezes, resulta em diagnóstico tardio (Baracho; Geronimo;Triani, 2019).…”
Section: Introductionunclassified